A Study On Deterioration- The Effect Of Altitude And Bio-Jet Fuel On Turbofan Engine Performance - Koh, Wei Chong (Universiti Sains Malaysia, 2017)
Air traffic and commercial aviation is very much expected to grow significantly annually in the future and thus it is a concern for all parties that not only the aircraft operation has an effect of the environment, but also the huge amount of investment being placed into aircraft maintenance programs. One important aspect of the aircraft engine is the performance deterioration and this will definitely affect both the environment and the economy. Therefore, these are the main aims of this research work. The first is to study the deterioration effects on aircraft engine performance, followed by the investigation of the effect on operational altitudes on the performance of the deteriorated engine, and lastly the investigation of the performance of bio-jet fuel on deteriorated engine. The CFM56-3 which is a typical two-spool high bypass ratio turbofan engine, which is widely used on the Boeing 737 and Airbus A320 family, is chosen as the test subject for this study. In addition, existing models and flight data were used for the validation of the present research model. Deterioration rate of the turbofan engine up to 0.1% per day is applied as a deterioration basis for all deterioration studies. Bio-jet fuels such as Jatropha Bio-synthetic Paraffinic Kerosene (JSPK), Camellina Bio-synthetic Paraffinic Kerosene (CSPK) and their blends with Jet-A were used as the fuel variants for the bio-jet fuel study. Results obtained on the performance deterioration study with conventional Jet-A fuel shows reduction in air mass flow rate, shaft speed, thrust, thrust specific fuel consumption and exhaust gas temperature with certain deterioration trends within a 30-day period. Also, when the altitudes as ambient conditions were varied, the thrust specific consumptions shows that it is at its lowest when operating at the altitude of 4000m, while thrust and air mass flow rate decreases as altitude increases because of lower air density. In comparison to Jet-A, utilizing bio-jet fuel in the turbofan engine with 0.1% deterioration rate is found to increase engine air mass flow rate, engine thrust and thrust specific fuel consumption due to high value of the fuel’s low heating value (LHV). Finally, a few additions to the current research framework is discussed in order to increase the simulation quality in the future, as well as to provide a more wide, comprehensive research and understanding on a more realistic representation of the study of gas turbine engine deterioration and the aspects that affect it.